A Comparative Study on Wellbore Pressure Transmission of Water and Carbon Dioxide during Fracturing. Issue 1 (August 2020) - Xiao, Caiyun; Ni, Hongjian; Zhao, Bo; Li, Ning
Abstract: Hydraulic fracturing is one of the most effective ways for the development of unconventional oil and gas resources, CO2 has been regarded as an excellent alternative to water as its broad application prospects in unconventional reservoir development and benefit for CO2 utilization. The wellbore pressure will keep rising before fracture initiation during hydraulic fracturing, and fluid properties have significant influence of wellbore pressure transmission especially for CO2 fracturing. In this paper, a wellbore pressure transmission model based on the definition of fluid compressibility is established and coupled with wellbore flow model of compressible fluid to calculate the borehole pressurization rate for water-based and CO2 fracturing. The model has been verified by field data. The results show that the borehole pressurization rate for both water-based and CO2 fracturing reveal rising trend as pump rate increasing, and borehole pressurization rate of water-based fracturing is 10∼20 times that of CO2 fracturing with same pump rate. Moreover, the borehole pressurization rate increases linearly with pump rate of water-based fracturing, but excessive pump rate might reduce borehole pressurization rate of CO2 fracturing. The research results can simulate more perceptions for the optimizing design of actual hydraulic fracturing operating.